(untitled) (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a neurological disorder that affects the neuropsychomotor development of children. The present study aims to identify the perception of parents and professionals about the use of Animal Assisted Therapy (AAT) as a therapeutic resource in interventions with children with ASD. This is a qualitative study, using a questionnaire, which was applied to parents and professionals with experience in caring for animal co-therapists. The study included eight parents of children with ASD aged between three and eleven years, who have been undergoing therapy with animals for more than a year, and seven professionals, including psychologists, physiotherapists, pedagogues and psychopedagogues. The results suggest that AAT has great potential as a therapeutic resource in reducing autistic symptoms in relation to communication, social interaction and affection, presenting behavioral changes after sessions and interaction with animals, from the perspective of parents and professionals. In this way, this study contributes to scientific advancement, the quality of life and well-being of people with ASD and their family members, and offers information to professionals who work with this specific group.